Letter (copy) : Ray Cox Memorial - Citrine, Walter, 1887-1983
042-0086-001 WMC/WJB/MS/186 International. 16th December, 1937. Mr. L. Witt, The Joint Council of the Southampton Trades Council, Labour Party & Co-operative Party, Prospect House, 160 Above Bar, Southampton. Dear Mr. Witt, RAY COX MEMORIAL. We are in receipt of your letter of the 13th instant enclosing further cheque value £7. 14. 5 for the fund for medical aid for Spain. We are very grateful to you and your colleagues for your magnificent response to our appeals. With regard to the Ray Cox Memorial, we have not forgotten our arrangement. At the last meeting of the I.F.T.U. Executive Committee meeting held in November we reminded the Secretary, Mr. W. Schevenels, of his promise to obtain a photograph for us. The only reply we received was that he was still "waiting" for it himself. Apparently he has not been to Spain recently as he had hoped to do. We can only send another letter to him and when we get his reply will forward it to you. Yours faithfully, General Secretary. 292/946/42/86